Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter 2 - Section 2.6 - Rational Functions and Their Graphs - Exercise Set - Page 399: 92


$\frac{-2}{(x+2)(x+3)}$, See graph.

Work Step by Step

Step 1. Factor the denominators and perform the subtraction to get: $f(x)=\frac{2}{(x+1)(x+2)}-\frac{4}{(x+1)(x+3)}=\frac{2(x+3)-4(x+2)}{(x+1)(x+2)(x+3)}=\frac{-2x-2}{(x+1)(x+2)(x+3)}=\frac{-2}{(x+2)(x+3)}$ with a hole at $(-1,-1)$ and $x\ne-3,-2$ Step 2. We can identify two vertical asymptotes as $x=-3$ and $x=-2$ Step 3. We can also identify a horizontal asymptote as $y=0$ and a y-intercept as $y=-\frac{1}{3}$ Step 4. Testing signs across the vertical asymptotes, we have $...(-)...(-3)...(+)...(-2)...(-)...$ Step 5. Based on the above results, we can graph the function as shown in the figure.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.